A novel Arabidopsis gene RGAT1 is required for GA‐mediated tapetum and pollen development. Issue 1 (30th March 2021) - Qian, Qian; Yang, Yuhua; Zhang, Wenbin; Hu, Yilong; Li, Yuge; Yu, Hao; Hou, Xingliang
Summary: The phytohormone gibberellin (GA) is critical for anther development. RGA, a member of the DELLA family of proteins that are central GA signalling repressors, is a key regulator of male fertility in plants. However, the downstream genes in GA–RGA‐mediated anther development remain to be characterised. We identified RGA Target 1 ( RGAT1 ), a novel Arabidopsis gene, that functions as an important RGA‐regulated target in pollen development. RGAT1 is predominantly expressed in the tapetum and microspores during anther stages 8–11, and can be directly activated by RGA and suppressed by GA in inflorescence apices. Both loss of function and gain of function of RGAT1 led to abnormal tapetum development, resulting in abortive pollen and short siliques. In RGAT1 ‐knockdown and overexpression lines, pollen abortion occurred at stage 10. Loss of RGAT1 function induced the premature degeneration of tapetal cells with defective ER‐derived tapetosomes, while RGAT1 overexpression delayed tapetum degeneration. TUNEL assay confirmed that RGAT1 participates in timely tapetal programmed cell death. Moreover, reducing RGAT1 expression partially rescued the tapetal developmental defects in GA‐deficient ga1‐3 mutant. Our findings revealed that RGAT1 is a direct target of RGA and plays an essential role in GA‐mediated tapetum and pollen development.